PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI DENGAN KOMUNIKASI SEBAGAI VARIABEL MODERATING - Mohklas . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
The purpose of this study was to examine and analyze the effect of the competence and motivation of the employee's performance with the moderated communication variables. The variables in this study consisted of four variables, namely: competence, motivation as independent variables, and communication modering variable, while the employee's performance as the dependent variable. The population in this study were all employees at the district office Gayamsari Semarang. Samples taken in this study as many as 52 people. Research data collection techniques by spreading questionnaire compiled systematically with multiple choice answers are easy to understand. The distribution of the questionnaire by means of a direct encounter conducted in the period from October to November 2015. The data were collected through a questionnaire to test the data analyst; validity and reliability, the classic assumption test followed by multiple regression analysis, test moderating variable by using MRA (Moderated Regression Analysis)